Reseña de: Quesada Quesada. José Joaquín, Iglesias de Jaén - Pérez-Schmid Fernández, Francisco José (Espacio Tiempo y Forma. Serie VII, Historia del Arte, 2022)
Reseña de: Quesada Quesada, José Joaquín, Iglesias de Jaén. Córdoba, Editorial Almuzara, 2021. ISBN: 978-84-18709-04-3, 227 pp.